MENAVIGASI TANTANGAN FISKAL: EFEKTIVITAS SUKUK SEBAGAI INSTRUMEN ALTERNATIF PEMBIAYAAN DEFISIT DI INDONESIA - Masruroh, Aniswatun; Fitrianto, Achmad Room (Islamic Economics Program, Faculty of Islamic Economics and Business, 2023)
In the past half-decade, Indonesia encountered its highest budget deficit in 2022, amounting to IDR 464.3 trillion or 2.38% of the nation's GDP, as reported by the Ministry of Finance. To counteract this, the government formulates the State Revenue and Expenditure Budget (APBN) annually, serving as a pivotal tool for national welfare and economic governance. Governed by fiscal policy, APBN orchestrates government revenue and spending to propel economic enhancement. This paper scrutinizes the efficacy of sukuk as a deficit financing alternative, considering policies, implementation strategies, targeting precision, and procedural efficiency. The study, covering the period from 2018 to 2023, accentuates sukuk's resilience amidst economic uncertainties. Key determinants of sukuk effectiveness include well-aligned policies with national objectives, collaborative execution involving diverse stakeholders, congruence with targeted goals, and streamlined processes adhering to legislative frameworks. The research further delves into the varied spectrum of sukuk instruments traded in the market, distinguishing between tradable and non-tradeable categories. Tradable sukuk exhibit liquidity advantages, while non-tradable sukuk offer price stability. Indonesia's substantial growth in sukuk from 2020 to January 2023 underscores its potential in a predominantly Muslim-populated country. This research method is qualitative with a literature study approach obtained from secondary data. The results of this research are that sukuk is very effective as an alternative financing method. This is proven by an increase in total assets in 2022 amounting to IDR 131.46 trillion from 68 issuers and there were 512 recorded emissions using a circulating nominal value of IDR 459.15 trillion and US 47.5 million